Secrets in our DNA [videorecording (DVD)] - Gray, Edward (Director); Gray, Edward (Director); Williams, Talithia ([publisher not identified], 2021)
Explores the increasing popularity of personal DNA analysis by companies like 23andMe and AncestryDNA and the unintended consequences of sharing our data with these rapidly growing online databases.